A Nonflammable Na+‐Based Dual‐Carbon Battery with Low‐Cost, High Voltage, and Long Cycle Life. Issue 36 (25th October 2018) - Jiang, Xiaoyu; Liu, Xingwei; Zeng, Ziqi; Xiao, Lifen; Ai, Xinping; Yang, Hanxi; Cao, Yuliang
Abstract: Dual‐carbon batteries provide a new perspective on energy storage technology due to their high voltage and low cost. Herein, a novel Na + ‐based dual‐carbon battery (Na + ‐DCB) is developed based on a nonflammable trimethyl phosphate (TMP) electrolyte with sodium bis(trifluoromethanesulfonate)imide salt (NaTFSI). As the molar ratio of NaTFSI/TMP increases to 1:2, the graphite cathode shows a high reversible capacity of 52.9 mAh g −1, excellent rate capability (21.0 mAh g −1 at 2000 mA g −1 ) and superstability cycling performance (≈100% capacity retention after 750 cycles). In addition, a stable solid electrolyte interface (SEI) film is formed on the surface of hard carbon anode by the preferential reductive decomposition of TFSI −, which suppresses decomposition of TMP. In this case, the Na + ‐DCB is capable to provide an operation voltage of 4.0 V and excellent electrochemical performance. This work provides new insights for developing new dual‐carbon batteries with safety, low cost, and absence of heavy metals. Abstract : A nonflammable phosphate electrolyte for Na + ‐based dual‐carbon batteries is reported. When the molar ratio of sodium bis (trifluoromethanesulfonate) imide to trimethyl phosphate increases to 1:2, the electrochemical decomposition of electrolyte solvent is greatly suppressed, thus the Na + ‐based dual‐carbon battery shows excellent cycling stability (71% capacity retention over 200 cycles) and high rate capability (46.6 mAh g −1 at 500 mAh g −1 ).